2012
DOI: 10.1007/s11999-011-2238-7
|View full text |Cite
|
Sign up to set email alerts
|

Similar Survival but Better Function for Patients after Limb Salvage versus Amputation for Distal Tibia Osteosarcoma

Abstract: Level III, retrospective comparative study. See the Guidelines for Authors for a complete description of levels of evidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
114
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(130 citation statements)
references
References 38 publications
(201 reference statements)
5
114
0
2
Order By: Relevance
“…The main complications include infection, fracture, nonunion, loosening, and so on. Amputation does not have the above complications, so it still has some value in the treatment of osteosarcoma [21].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The main complications include infection, fracture, nonunion, loosening, and so on. Amputation does not have the above complications, so it still has some value in the treatment of osteosarcoma [21].…”
Section: Discussionmentioning
confidence: 99%
“…The MSTS scores at 6 months post operation were 10.60 ± 1.65 (7)(8)(9)(10)(11)(12)(13) in the amputation group, 22.45 ± 1.82 (19)(20)(21)(22)(23)(24)(25)(26) in the massive osteoarticular allograft group, and 25.23 ± 1.17 (22)(23)(24)(25)(26)(27) in the tumor resection and artificial joint replacement group (table 2).…”
Section: Function Outcomesmentioning
confidence: 99%
“…Over the course of the 1950s, while the five-year survival rates initially were around 20% and amputation was the first choice in extremity malignant tumors, the rates increased to 60-70% through use of adjuvant chemotherapy and radiotherapy, and amputation was replaced with limb salvage surgery (LSS) [5][6][7]. While LSS has advantages such as reconstruction stability and functionality, it also has disadvantages such as fractures and fixation loss [8].…”
Section: Discussionmentioning
confidence: 99%
“…[13,14] Several studies reported the survival rates after limb-salvage range from 100% to 50% at 6-288 months, [15,16] whereas those for amputation range from 100% to 84% at 36-60 months. [4,17] Thus, whether the relapse, 5-year survival and metastasis the same or not between limb-salvage and amputation in the treatment of patients with limited stage EnnekingⅡpathologic fracture osteosarcoma was not known.…”
Section: Discussionmentioning
confidence: 99%
“…[3] Several studies have evaluated the difference between limb-savage surgery and amputation in patients with high-grade no-metastatic osteosarcoma and not shown a significant difference in aspects of survival and local recurrence rate. [3,4] But whether the relapse, 5-year survival and metastasis rate between limb-salvage and amputation in the treatment of patients with limited stage EnnekingⅡ pathologic fracture osteosarcoma patients were not known. Here, we performed this meta-analysis based on published clinical trials to further explore the clinical efficacy between limb-salvage and amputation in the treatment of patients with limited stage EnnekingⅡ pathologic fracture osteosarcoma patients.…”
Section: Introductionmentioning
confidence: 99%